2011
DOI: 10.2174/1874256401105010047
|View full text |Cite
|
Sign up to set email alerts
|

Lipofuscin-Like Substance Involved in Pericarp Browning of Postharvest Litchi Fruit During Storage

Abstract: Litchi (Litchi chinensis Sonn.) is a subtropical fruit of high commercial value in international trade. However, litchi fruit after harvest can rapidly lose their bright red skin color and turn brown with increasing storage time at ambient temperature. Postharvest browning of litchi fruit is mainly attributed to the degradation of anthocyanins and the oxidation of phenolics. In this study, the contents of lipofuscin-like substance in relation to the levels of anthocyanins and (-)-epicatechin, and browning inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…A lipofuscin‐like (lipid‐associated yellow granules) material is the result of oxidation of cellular membranes and contents via lipid hydroperoxides, malondialdehyde, and protein oxidation. Similar changes during senescence are also reported in pericarp browning (S. Yang et al., 2011). During storage of 72–144 h, the relative content of the lipofuscin‐like substance increased by 51%, while (‐)‐epicatechin decreased by 41% and anthocyanins by 98%.…”
Section: Postharvest Physiologysupporting
confidence: 84%
“…A lipofuscin‐like (lipid‐associated yellow granules) material is the result of oxidation of cellular membranes and contents via lipid hydroperoxides, malondialdehyde, and protein oxidation. Similar changes during senescence are also reported in pericarp browning (S. Yang et al., 2011). During storage of 72–144 h, the relative content of the lipofuscin‐like substance increased by 51%, while (‐)‐epicatechin decreased by 41% and anthocyanins by 98%.…”
Section: Postharvest Physiologysupporting
confidence: 84%
“…LFLP mainly comes from reactive carbonyl species (RCS; from lipid oxidation products and reducing sugars or their oxidation products) and can combine with macromolecules containing free amino group within cells, producing Schiff bases, 1,4‐dihydropyridines or 2‐hydroxy‐1,2‐dihydropyrrol‐3‐ones and displaying autofluorescent properties . Currently, a few studies have been reported, mainly in potatoes, senescing cotyledons, bananas and litchis . LFLP have been shown to accumulate with increasing age in various plants, and the LFLP accumulation is always positively correlated with lipid peroxidation processes.…”
Section: Introductionmentioning
confidence: 99%